Cognitive impairment and functional change in COVID-19 patients undergoing inpatient rehabilitation. Issue 3 (September 2021) - Patel, Ruchi; Savrides, Irene; Cahalan, Christine; Doulatani, Gargi; O'Dell, Michael W.; Toglia, Joan; Jaywant, Abhishek
Abstract : Cognitive impairment is increasingly recognized as a sequela of COVID-19. It is unknown how cognition changes and relates to functional gain during inpatient rehabilitation. We administered the Montreal Cognitive Assessment (MoCA) at admission to 77 patients undergoing inpatient rehabilitation for COVID-19 in a large US academic medical center. Forty-five patients were administered the MoCA at discharge. Functional gain was assessed by change in the quality indicator for self-care (QI-SC). In the full sample, 80.5% of patients exhibited cognitive impairment on admission, which was associated with prior delirium. Among 45 patients with retest data, there were significant improvements in MoCA and QI-SC. QI-SC score gain was higher in patients who made clinically meaningful changes on the MoCA, an association that persisted after accounting for age and delirium history. Cognitive impairment is frequent among COVID-19 patients, but improves over time and is associated with functional gain during inpatient rehabilitation.